Prediction of early acute kidney injury after trauma using prehospital systolic blood pressure and lactate levels: A prospective validation study. Issue 1 (January 2022) - Nasu, Toru; Ueda, Kentaro; Kawashima, Shuji; Okishio, Yuko; Kunitatsu, Kosei; Iwasaki, Yasuhiro; Kato, Seiya
Highlights: Acute kidney injury (AKI) is common in post-traumatic organ dysfunction. We showed the prehospital systolic blood pressure and arterial lactate were independent predictors of AKI after trauma. We performed a prospective validation analysis of 403 patients. These are associated with the early onset of acute kidney injury after trauma. These may be early predictors of the effects of treatment to prevent acute kidney injury. Abstract: Background: Acute kidney injury (AKI) after trauma is a major complication independently associated with a prolonged hospital stay and increased mortality. We previously reported that the prehospital systolic blood pressure (SBP) and early hospital arterial lactate level, along with specific cut-off values, show good performance in the early prediction of AKI using AUC-ROC [1] . The purpose of this study was to prospectively validate whether or not these parameters are predictive of newly occurring AKI after trauma. Methods: This was a prospective review of trauma patients who were admitted to a single trauma center from January to December 2019. Patients who were <16 years old, who had burns, and who had chronic kidney disease were excluded. AKI was defined according to the Risk, Injury, Failure, Loss of the kidney function, and End-stage kidney disease (RIFLE) classification based on serum creatinine alone. Patients with a low prehospital SBP (≤126 mmHg) and high lactate levels (≥2.5 mmol/L) were defined as the high-risk group, and other patients were defined as the low-risk group. Results: A total of 489 trauma patients were admitted to our center, of whom 403 were eligible for the study. The high-risk group consisted of 38 patients, and the low-risk group consisted of 365 patients. The incidence of severe AKI in Stage Injury and Failure was significantly higher in the high-risk group (5 patients, 13.2%) than in the low-risk group (7 patients, 1.9%), with an odds ratio of 7.75 and 95% confidence interval of 2.33–25.77. Conclusions: These predictors showed good performance in the early prediction of severe AKI after trauma. Early prediction of the high-risk groups for severe AKI after trauma prompting early treatment may help improve the prognosis of trauma patients.